If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -75 = -12x + 135 Reorder the terms: -75 + 3x = -12x + 135 Reorder the terms: -75 + 3x = 135 + -12x Solving -75 + 3x = 135 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -75 + 3x + 12x = 135 + -12x + 12x Combine like terms: 3x + 12x = 15x -75 + 15x = 135 + -12x + 12x Combine like terms: -12x + 12x = 0 -75 + 15x = 135 + 0 -75 + 15x = 135 Add '75' to each side of the equation. -75 + 75 + 15x = 135 + 75 Combine like terms: -75 + 75 = 0 0 + 15x = 135 + 75 15x = 135 + 75 Combine like terms: 135 + 75 = 210 15x = 210 Divide each side by '15'. x = 14 Simplifying x = 14
| -30z-0.8=-40z+1.7 | | 4x-11-6x+1=19-3x-1-3x | | -30z-0.8=40z+1.7 | | y=ln(5x^4-3x) | | y=-3f(x+5)+3 | | -8k-12= | | 12-0.4n= | | 96=w^2+4w | | 4x+54=180 | | 2/7x-1/6=8 | | 3x+21+3x-2=52-3x+39 | | 9x-15=11x+23 | | 8-2x=2x-8-8x | | 84=b^2-5b | | -7a=-11a-68 | | 4q^2-6q-4q^2+6q=4q^2-9 | | f(x)=2x^3+4x^2 | | 42=b^2-5b | | 8r+12ry-3xr-2xy= | | (-9x+2)-(-3x+-5)= | | x^2-3=-5 | | 9(2g+5)= | | 12x^5+15x^4+9X^2-4x=0 | | (1-z)(3z+5)=0 | | 7x+9y=-3 | | -22+n=50 | | 10x-5=8x-15 | | 7=6w+w | | 15w-8w=56 | | 42a^8-14a^8= | | 2p+-13p-17p=-18 | | 2(3x+6)-4= |